Pengaruh Kualitas Produk, Harga, Cita Rasa Dan Promosi Terhadap Kepuasan Konsumen Di Rumah Makan Mbak Siti - Amir Hamzah Siregar, Susana, Zuriani Ritonga, Desmawati Hasibuan, Elvina (Journal Economy and Currency Study (JECS), 2021)
The purpose of this study was to determine the effect of product quality, price, taste and promotion on consumer satisfaction at Mbak Siti's restaurant in Sosopan Village, Kotapinang District, Labuhanbatu Selatan Regency. The sample in this study amounted to 30 people. The analytical method used is descriptive analysis, classical assumption test, multiple linear regression analysis, t test, f test, and coefficient of determination and this data is processed using the IBM SPSS Statistics 21 program. Hypothesis test results show that partially the product (X1) has a positive and significant effect on consumer satisfaction, this can be seen from the tcount value for product quality is tcount 0.009> ttable 2.05954, with a significant value of 0.993 <0.05. Hagra (X2) has a positive and significant effect on consumer satisfaction, this can be seen from the tcount value for price is tcount 2.273> ttable 2.05954, with a significant value of 0.32 <0.05. Taste (X3) has a positive and significant effect on consumer satisfaction, this can be seen from the tcount value for taste is tcount 0.541> ttable 2.05954, with a significant value of 0.593 <0.05. Promotion (X4) has a positive and significant effect on customer satisfaction, this can be seen from the tcount value for promotion is tcount 6.794> ttable 2.05954, with a significant value of 0.000 <0.05. The value of Ftable in the 4: 26 distribution is 2.74, so based on table 4.14 it can be seen that the Fcount value is 36.656> 2.70, and a significant value is 0.000 <0.05, this shows that simultaneously the Independent Variable has a positive and significant effect on the Dependent Variable.